Toward more sustainable metaphors of writing program administration - Wilkes, Lydia; Mina, Lilian W.; Poblete, Patti (Utah State University Press, 2023)
"Toward More Sustainable Metaphors of Writing Program Administration builds on forty years of conversations about metaphors by presenting twelve chapters that reclaim and revise established metaphors; offer new metaphors based on sustainable, relational, or emotional labor practices and phenomena; and reveal the improvisational nature of WPA work"--